P17.13.A Verteporfin inhibits autophagy in glioblastoma cell lines. (5th September 2022) - Casati, G; Giunti, L; Iorio, A; Marturano, A; Sardi, I
Abstract: Background: Glioblastoma (GBM) is the most common primary brain tumor with a poor prognosis, characterized by a high cellular heterogeneity and invasiveness. Multi-drug resistance (MDR), the blood brain barrier (BEE) and DNA repair systems let the survival of tumor cells, making the treatment with chemo and radiotherapy not effective. Autophagy is a physiological mechanism that allows the recycling of damaged proteins and organelles, in order to protect the correct cell turnover. However, in GBM this process promotes survival and proliferation in stressful conditions such as after a chemo and / or radiotherapy treatment. The Hippo pathway is an extremely important molecular signaling because it is involved in various tumorigenesis processes, for instance the epithelium-mesenchymal transition (EMT), in the increase of stemness, mechanotransduction and chemoresistance. Material and Methods: The modulation of autophagy was evaluated in GBM cell lines (U87MG, T98G and A172) exploiting a fluorescent detection that allowed the quantification of the autophagosomal activity present into the cell lines. The rate of autophagy was assessed after the cell lines pharmacological treatment with Hippo pathway inhibitors, Verteporfin 2uM (VP) for 24h, Latrunculin 0, 5uM (LAT) for 3h and Cytochalasin 1uM (CIT) for 3h, with Doxorubicin 0, 5uM (DOX) for 24h and with the drugs combination (DOX-VP, DOX-LAT and DOX-CIT). Moreover, the expression of the autophagy marker LC3II / I was evaluated in all three GBM cell lines by Western Blotting (WB) experiments. To perform this technique, the cells were treated with DOX and Hippo pathway inhibitors respecting the pharmacological treatment previously used. Then, the proteins were extracted, quantified and finally the WB was performed. Results: The results obtained showed that the three GBM cell lines without any drugs were marked by high levels of autophagy, similar to the cells treated with Rapamycin, an autophagy inducer. Moreover, the autophagy rate was definitely reduced after treatment with VP and DOX-VP in all three cell lines, including the chemoresistant T98G. Conversely, the other two Hippo pathway inhibitors (LAT-CIT) and DOX did not significantly change the rate of autophagy. The expression of LC3II / I was particularly low after treatment with VP and DOX-VP in all three cell lines while the other two inhibitors did not significantly change its expression. Conclusion: In conclusion, these data demonstrated that the three GBM cell lines (U87MG, T98G and A172) are characterized by high levels of autophagy and the inhibition of the Hippo pathway with VP and especially the combination DOX-VP reduced the activation of this protumoral molecular mechanism in GBM cell lines.